Epistemological perspectives in the meta-research context: a study on research on education policies (Revista de Estudios Teóricos y Epistemológicos en Política Educativa, 2021)
This meta-research aimed to identify the epistemological perspective made explicit in 56 Master’s thesis of the Research Line 1 – “Education Policies, History and Organization of Education”, of the Graduate Program in Education at the Universidade Estadual do Centro-Oeste (UNICENTRO), formulated in the period from 2014 to 2018, based on the concepts of combined theorization and added theorization (MCLENNAN, 1996) and in the proposal of meta-research in Education Policy, through the systematic reading of the selected sample (MAINARDES, 2017, 2018a, 2021). Regarding the results of this study, it is highlighted those 51 Master’s students (91.04%) indicated authors or traditions/theoretical matrices, not making reference to the epistemological perspectives used in the dissertations. The other five dissertations (8.96%) did not make such notes; thus, they encompassed different authors who supported the analyzes performed. Given the above, four of these works (7.18%) were classified as combined theorization, as they combined authors who supported a consistent framework for the analysis. One Master’s thesis (1.78%) performed little theoretical analysis, which culminated in a research classified as added theorization. The explicitness of the historical-dialectical materialism stood out as the most used theoretical perspective in the analyzed research, a total of 35 dissertations (62.5%). Thus, it was verified that the pieces of research formulated within the scope of the Graduate Program in Education at UNICENTRO), although mentioning the theoretical perspectives used, could be classified as studies of combined theorization or added theorization, as they made use of different authors and different theories to formulate the theoretical framework.Keywords: Meta research. Epistemological perspective. Research on education policies.